Debris entrainment and landform genesis during tidewater glacier surges. Issue 8 (22nd August 2015) - Lovell, Harold; Fleming, Edward J.; Benn, Douglas I.; Hubbard, Bryn; Lukas, Sven; Rea, Brice R.; Noormets, Riko; Flink, Anne E.
Abstract: The englacial entrainment of basal debris during surges presents an opportunity to investigate processes acting at the glacier bed. The subsequent melt‐out of debris‐rich englacial structures during the quiescent phase produces geometrical ridge networks on glacier forelands that are diagnostic of surge activity. We investigate the link between debris entrainment and proglacial geomorphology by analyzing basal ice, englacial structures, and ridge networks exposed at the margins of Tunabreen, a tidewater surge‐type glacier in Svalbard. The basal ice facies display clear evidence for brittle and ductile tectonic deformation, resulting in overall thickening of the basal ice sequence. The formation of debris‐poor dispersed facies ice is the result of strain‐induced metamorphism of meteoric ice near the bed. Debris‐rich englacial structures display a variety of characteristics and morphologies and are interpreted to represent the incorporation and elevation of subglacial till via the squeezing of till into basal crevasses and hydrofracture exploitation of thrust faults, reoriented crevasse squeezes, and preexisting fractures. These structures are observed to melt‐out and form embryonic geometrical ridge networks at the base of a terrestrially grounded ice cliff. Ridge networks are also located at the terrestrial margins of Tunabreen, neighboring Von Postbreen, and in a submarine position within Tempelfjorden. Analysis of network characteristics allows these ridges to be linked to different formational mechanisms of their parent debris‐rich englacial structures. This in turn provides an insight into variations in the dominant tectonic stress regimes acting across the glacier during surges. Key Points: We investigate basal ice and englacial structures at a surge‐type glacier The formation of both is linked to tectonic processes during the surge Melt‐out of englacial structures produces proglacial ridge networks